(untitled) (Journal of Enam Medical College, 2021)
Background: Excessive menstrual bleeding called menorrhagia is a common presentation of females seeking medical attention. Normally there is considerable variation in menstrual cycle length, duration and flow. Objective: To find out the assocation of fibroids in patients presenting with menorrhagia. Materials and Methods: This cross-sectional prospective study was done from January to June 2013 among the female patients admitted in the department of Gynaecology & Obstetrics in Dhaka Medical College & Hospital. Patients presented with the complaints of menorrhagia and treated by surgical management were included. Results: Total 96 patients were included. The age range was 28–49 years with mean age 41.08 ± 5.174 years. In 92 (46.5%) patients excessive per vaginal bleeding was noted. Pain during menstruation was another major complaint (45, 46.5%). Lower abdominal heaviness was reported in 32 patients (16.2%). In about half of the patients (49%) uterine fibroid was diagnosed. In 29 patients (30.2%) adenomyosis was the finding. Out of 47 fibroid cases 39 (83%) had per vaginal bleeding history. Only 10 patients without fibroid experienced pervaginal bleeding. Chi-squared test was done to see whether there was any association between these two variables and the result was highly significant (p<0.001). Conclusion: As medical treatment is disappointing and surgery is the mainstay of treatment of menorrhagia caused by fibroids, diagnosis should be confirmed by different imaging techniques. Advancement in the field of imaging like saline infusion sonohysterography and hysteroscopy helps greatly to diagnose submucous fibroids and save patients from undue prolongation of medical treatment. J Enam Med Col 2020; 10(2): 99-103